Household resilience capacity and food security: Evidence from Kyrgyzstan - Bekhzod Egamberdiev; Ihtiyor Bobojonov; Lena Kuhn; Thomas Glauben (Food Security, 2023)
Commonly, resilience against external shocks is treated as a household or community capacity. Resiliency against food insecurity is of particular importance for rural household under the impression of recent price surges and supply chain disruptions. The aim of this paper is to analyze the effect of household resilience capacity on food security outcomes in Kyrgyzstan, using individual, household and community datasets of the “Life in Kyrgyzstan” panel survey for several waves from 2011 to 2016. Firstly, a resilience capacity index to food insecurity was estimated through key determinants or pillars under the Resilience Index Measurement and Analysis (RIMA) II methodology, while latent analysis was used to classify shocks. The effect of resilience capacity on food security outcomes was estimated along an instrumental variable approach. Our results suggest that resilience capacity serves to improve food security status and decrease the proneness of households to suffering from food insecurity in the presence of shocks. Furthermore, the interaction between resilience capacity and shocks was included to explain whether the negative effect of the shocks is weakened by resilience. The findings confirm that resilience capacity is able to mitigate the adverse effects of shocks on food security outcomes; moreover, it is sufficient to resist a decline in food security. Following the large contributions of social safety nets and adaptive capacity to the resilience capacity index, policy efforts should be focused on increasing income generating capacity, networking, migration, and education level of households to strengthen resilience to food insecurity.
Keywords: 630; resilience; food security; latent class; Central Asia